AGE, PATTERN AND SYMPTOMS OF MENOPAUSE AMONG RURAL WOMEN OF LAHORE - Yahya, Samira; Rehan, N. (Journal of Ayub Medical College Abbottabad, 2002)
Background. The occurrence and timing of reproduction-related events such as menarche, first birth and menopause play major roles in a woman’s life. The age at final natural menstrual period is an important risk indicator for subsequent morbidity and mortality. However, the age of natural menopause and frequency of various menopausal symptoms differ in different societies. The concept of local biologies has been put forward to account for such inter-societal and intra-societal differences. The present study was undertaken to explore the age at menopause and symptom complex associated with menopause. Methods: The data for this cross-sectional study were collected from a geographically defined rural population of 28,419 individuals living in 20 villages situated about 30 KM outside Lahore. A systematic random sample of 130 women was drawn from those 1337 women, who had reached natural menopause. In-depth interviews were conducted in local dialect. Results: The mean age at menopause was 49±3.6 years; the median being 50 years. The majority of women (22.3%) reached menopause at 50 years followed by 13.9%, who became menopausal at 49 years. In 66.2% cases, the onset of menopause was sudden. Among those, who had a gradual transition, the duration of climacteric ranged from 2 to 30 months. The symptoms associated with menopause were lethargy (65.4%), forgetfulness (57.7%), urinary symptoms (56.2%), agitation (50.8%), depression (38.5%), insomnia (38.5%) hot flushes (36.2%) and dysparunea (16.9%). Conclusions: The median age of menopause in our study is lower than that reported for Caucasian, Thai and Malaysian women; similar to figures from Africa and South America; but higher than that reported from Iran, Egypt, Turkey and UAE. The frequency of various symptoms was comparatively lower than observed among Caucasian populations. The data highlights the need for studying ’˜local biologies’ and understanding the social and cultural basis of these differences. Key Words: Menopause. Local biologies. Menopausal symptoms.